Increased Purchases of Insurance Products Based on Factors That Affect Customer Trust (Study on Banccasurance in Greater Jakarta, Indonesia) - Wasi Bagasworo; Sandi Simatupang (STIE Indonesia Banking School, 2022)
The objective of this research is to analyze the influence of service quality of salesperson, trust in an insurance company, trust in a seller's bank on the level of customer trust for Increased purchases of bancassurance products in greater Jakarta, Indonesia. The sample consists of Banks which are categorized as banking customers who have purchased bancassurance products in the Greater Jakarta area. The technique of analysis used for this research is the structural equation model. This research has been analyzed with an AMOS 20 program, and during the significance test, it indicated that fixed effect was the most appropriate method. The result of this research shows that the service quality of the salesperson shows a significant positive effect on the level of customer trust, the credibility of the seller bank shows a significant positive effect on the level of customer trust, and the credibility of the insurance company shows a significant positive effect on the level of customer confidence, level of customer trust shows a significant positive effect on purchasing decisions .